Assessment of Cytotoxicity and Genotoxicity of Plasma-Treated Perfluorooctanesulfonate Containing Water Using In Vitro Bioassays - Markus Windisch; Roman Klymenko; Hannah Grießler; Clemens Kittinger (Toxics)
The contamination of ground and surface waters with per- and polyfluoroalkyl substances (PFASs) is of major concern due to their potential adverse effects on human health. The carbon–fluorine bond makes these compounds extremely stable and hardly degradable by natural processes. Therefore, methods for PFAS removal from water are desperately needed. In this context, plasma treatment of water has been proposed as an effective method with reported removal rates exceeding 90%. However, the high reactivity of plasma discharge results in the formation of many reactive species, like radicals, ozone, or even solvated electrons, which lead to a complex reaction cascade and, consequently, to the generation of a wide variety of different chemical products. The toxicological properties of these PFAS breakdown products are largely unknown. The present study focuses on a toxicological assessment of PFAS-containing plasma-treated water samples. Aqueous solutions of long-chain perfluorooctanesulfonate (PFOS) were treated with various plasma-atmospheric regimes. Subsequently, plasma-treated water samples were subjected to in vitro bioassays. Cytotoxicity and genotoxicity were assessed with the MTS assay using human liver cells (HepG2) and the Ames MPFTM assay using Salmonella Typhimurium strains. Our results demonstrate varying cyto- and genotoxic properties of water containing PFAS breakdown products depending on the atmosphere present during plasma treatment. Based on the results of this study, the atmosphere used during plasma treatment affects the toxicological properties of the treated sample. Further studies are therefore needed to uncover the toxicological implications of the different treatment parameters, including the PFAS starting compound, the atmosphere during treatment, as well as the quantity of plasma energy applied.